Digital Transformation in Government Services: Enhancing Efficiency, Accessibility, and Citizen Experience: A Case Study of The United Arab Emirates (UAE) - AlHaiyas, Khawla Mossa Abdulla (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to highlight the topic of "Digital Transformation in Government Services: Enhancing Efficiency, Accessibility, and Citizen Experience ", as digital transformation is one of the principal axes of digital government initiatives. This study reviewed the stages of transition from E-Government to digital government, highlighting the most essential concepts and terms, problems, and challenges related to digital transformation. This study sheds light on the importance of digital transformation, highlighting its impact on quality of life and customer satisfaction. It also deals with organizational aspects and reviews the experiences of the United Arab Emirates. The study concluded that the Digital Transformation represents a qualitative leap in the government work system, contributing to reduced traffic congestion and a decrease in widespread accidents. The most important thing is to provide digital services via the Internet and other networks intelligently and efficiently, faster, cheaper, better, and more securely, with unprecedented new horizons. The study also identified the most significant benefits of digital transformation, including cost savings, time efficiency, reduced effort, lower government expenditures, reduced traffic congestion, and fewer widespread accidents. Digital government increases the confidence of citizens and all customers. It provides opportunities for interaction, transparency, and participation between the government and the people, as well as the exchange of information among the people. And it ensures a safe and decent life for all UAE residents, without exception. The study concluded that the costly infrastructure is one of the most prominent disadvantages of digital government, as it requires strong infrastructure, reliable and secure systems, and the connection of all users’ mobile devices to the Internet to access services.